Developing structured interactive multimedia applications with HTML5 - Workman, Robert; Podnar, Hrvoje (EdMedia: World Conference on Educational Media and Technology, 2012)
Keywords: dept.csc; ⛔ No DOI found

Genetic algorithm for network cost minimization using threshold based discounting - Podnar, Hrvoje; Skorinkapov, Jadranka (Journal of Applied Mathematics and Decision Sciences, 2003)
We present a genetic algorithm for heuristically solving a cost minimization problem applied to communication networks with threshold based discounting. The network model assumes that every two nodes can communicate and offers incentives to combine flow from different sources. Namely, there is a prescribed threshold on every link, and if the total flow on a link is greater than the threshold, the cost of this flow is discounted by a factor α. A heuristic algorithm based on genetic strategy is developed and applied to a benchmark set of problems. The results are compared with former branch and bound results using the CPLEX® solver. For larger data instances we were able to obtain improved solutions using less CPU time, confirming the effectiveness of our heuristic approach. Copyright© 2003, Lawrence Erlbaum Associates, Inc.
Keywords: Genetic algorithm; Mixed integer programming; Network design; Threshold based discounting; dept.csc

An application of a genetic algorithm for throughput optimization in non-broadcast WDM optical networks with regular topologies ∗ - Podnar, Hrvoje; Skorin-Kapov, Jadranka (Mathematical Communications, 2002)
Keywords: dept.csc; ⛔ No DOI found

Core node location problem: heuristic solvability via tabu search - Skorin-Kapov, Darko; Skorin-Kapov, Jadranka; Podnar, Hrvoje (2010)
Keywords: dept.csc; ⛔ No DOI found

Geospatial visualization of student population using Google™ Maps - Podnar, Hrvoje; Gschwender, Adam; Workman, Robert; Chan, Jian (Journal of Computing Sciences in Colleges, 2006)
Keywords: dept.csc; ⛔ No DOI found